MENELAAH KEMBALI GAGASAN PEMIKIRAN DAN PERJUANGAN AHMAD SYAFII MAARIF JALAN TENGAH KEBERAGAMAN - Wandi Wandi; M Arif Musthofa; Khusnul Yatima (Universitas Veteran Bangun Nusantara, 2019)
This research was specifically written as a result of reflection on diversity in Indonesia at this time, where friction in the name of ethnicity, race, religion and even the issue of state always appear in the public sphere, departing from the problem above, the author wants to